2020
DOI: 10.3390/cancers13010086
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody-Based Immunotherapy and Its Role in the Development of Cardiac Toxicity

Abstract: Immunotherapy is one of the most effective therapeutic options for cancer patients. Five specific classes of immunotherapies, which includes cell-based chimeric antigenic receptor T-cells, checkpoint inhibitors, cancer vaccines, antibody-based targeted therapies, and oncolytic viruses. Immunotherapies can improve survival rates among cancer patients. At the same time, however, they can cause inflammation and promote adverse cardiac immune modulation and cardiac failure among some cancer patients as late as fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Hypertension is common cardiovascular toxicity ( 9 ). We reviewed the relevant literature and found that no study reported the effect of ICIs therapy on the risk of hypertension, so we counted the incidence of hypertension in the included study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypertension is common cardiovascular toxicity ( 9 ). We reviewed the relevant literature and found that no study reported the effect of ICIs therapy on the risk of hypertension, so we counted the incidence of hypertension in the included study.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular toxicity of PD-1/PD-L1 inhibitors includes hypertension, myocarditis, arrhythmia, heart failure, myocardial infarction, pericardial effusion and cardiac arrest (8)(9)(10). We performed statistics on several cardiovascular toxicities included in the study, and the results showed that the incidence of all-grade myocarditis in the patients undergoing PD-1/PD-L1 inhibitors monotherapy was 0.13%, myocardial infarction 0.11%, pericardial effusion 0.08%, arrhythmia 0.17%, heart failure 0.11%, cardiac arrest 0.06% and hypertension 0.21%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody-based immunotherapy has been a major and rational therapeutic strategy in the clinical management of oncology ( 209 , 210 ). In clinical practice, therapeutic mAbs have a limited effectiveness in the treatment of solid tumours due to their large molecular weight, but a high degree of targeting ( 198 ).…”
Section: Application Of Monoclonal Antibodies In Tumour Therapymentioning
confidence: 99%
“…The treatment of the cancer uses various methods such as surgery, radiotherapy [18], immunotherapy, or chemotherapy [19]. In the case of immuno-or chemotherapy it is crucial to develop a method of targeted delivery of specific antibodies, antisense nucleic acids, or chemotherapeutic drugs inside the affected tissues [20]. This approach can help in avoiding the undesirable toxic effect of drugs on normal, healthy cells.…”
Section: Introductionmentioning
confidence: 99%